Plasma‐Soluble Biomarkers for Fibrodysplasia Ossificans Progressiva (FOP) Reflect Acute and Chronic Inflammatory States. (24th January 2022) - Pignolo, Robert J; McCarrick‐Walmsley, Ruth; Wang, Haitao; Qiu, Shirley; Hunter, Jeffrey; Barr, Sharon; He, Kevin; Zhang, Hui; Kaplan, Frederick S
ABSTRACT: Fibrodysplasia ossificans progressiva (FOP) is a progressive, debilitating genetic disease in which skeletal muscle and connective tissue is episodically replaced by heterotopic bone. Discovery of surrogate biomarkers of disease (genotype)‐related and flare‐up‐associated activity of FOP in a readily accessible matrix, such as plasma, would facilitate an understanding of the complex pathophysiology of FOP, aid patient care, and provide a valuable tool for the development and monitoring of potential therapeutics. In a case–control study, using a carefully collected and curated set of plasma samples from 40 FOP patients with the classic ACVR1 R206H mutation and 40 age‐ and sex‐matched controls, we report the identification of disease‐related and flare‐up‐associated biomarkers of FOP using a multiplex analysis of 113 plasma‐soluble analytes. Adiponectin (implicated in hypoxia, inflammation, and heterotopic ossification) as well as tenascin‐C (an endogenous activator of innate immune signaling through the TLR4 pathway and a substrate for kallikrein‐7) were highly correlated with FOP genotype, while kallikrein‐7 was highly correlated with acute flare‐up status. Plasma‐soluble biomarkers for FOP support a flare‐up‐related acute inflammatory phase of disease activity superimposed on a genotypic background of chronic inflammation. © 2021 American Society for Bone and Mineral Research (ASBMR).